The effect of the educational props strategy on developing the attitude towards social sciences among fifth graders - Mohannad Jassim Alkhazraji / Asmahan Anber Lazim Moker ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The current research aims to identify (the effect of the educational pillars strategy on developing the trend towards social sciences for fifth grade students) and in order to verify this goal, the researcher formulated the following hypotheses:1- There is no statistically significant difference at the level of significance (0.05) between the average scores of the experimental group students who are taught according to the educational pillars strategy and the average scores of the control group that studies the social subject according to the usual method in the post-altitude scale test.2- There is no statistically significant difference at the level of significance (0.05) between the average scores of the experimental group students who study the social subject according to the strategy of educational pillars in the scale of the pre and post direction.The researcher used the experimental method to achieve the goal and hypothesis of the research, and the current research was limited to a sample of fifth grade students in the government primary day schools of the Maysan Education Directorate for the academic year 2018/2019.The experiment was applied in the second semester, as the actual teaching started (21/2/2019) to (23/4/2019). To obtain the results, the data was statistically processed using the t-test for two independent samples, and the results showed the following:- The students of the experimental group who study according to the strategy of educational pillars outperformed the students of the control group who study the subject of social sciences according to the usual method in the dimension scale.Interpretation of the results of the trend towards matterThe results of the research showed the superiority of the experimental group that was studied with the educational props strategy in testing the attitude towards the material. The reasons are attributed to the following:1 - This strategy achieved a sense of fun and excitement among the students and a good interest in learning, which was reflected positively on their attitude towards the subject of social studies.2- The topics of the second unit of the social book focused on the emotional aspects, whether religious or national, and the use of the props strategy and the visual scenes and images it presented, which led to the formation of a positive trend towards the subject of social studies.